2021
DOI: 10.31234/osf.io/r8m9b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neural correlates of inhibitory control in 10-month-old infants: a functional near-infrared spectroscopy study

Abstract: Inhibitory control, a core executive function, emerges in infancy and develops rapidly across childhood. Methodological limitations have meant that studies investigating the neural correlates underlying inhibitory control in infancy are rare. Employing functional near-infrared spectroscopy alongside a novel touchscreen task that measures response inhibition, this study aimed to uncover the neural underpinnings of inhibitory control in 10-month-old infants (N = 135). We found that when inhibition is required, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…We do however acknowledge that the current report presents no evidence for test-retest reliability in the classical sense of establishing that performance is stable across a short period of time, typically 1–2 weeks. ECITT accuracy test-retest reliability has been assessed in infants, and was found to be significant but modest [ 71 , 72 ]. We expect test-retest reliability to be higher in toddlers where data is generally less noisy, but no data is presently available on short-term test-retest reliability in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do however acknowledge that the current report presents no evidence for test-retest reliability in the classical sense of establishing that performance is stable across a short period of time, typically 1–2 weeks. ECITT accuracy test-retest reliability has been assessed in infants, and was found to be significant but modest [ 71 , 72 ]. We expect test-retest reliability to be higher in toddlers where data is generally less noisy, but no data is presently available on short-term test-retest reliability in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…This study also indicated that, by 16 months of age, performance on the ECITT correlates significantly with performance on the A-not-B task [ 71 ]. In a separate sample of 135 infants, we used the ECITT in combination with functional near-infrared spectroscopy and found evidence that, already at 10 months, infants activate classic response inhibition areas of the brain while performing the task [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, future research may follow up on whether social contents that are not specifically emotional can also facilitate conflict processing. In this context, it would further be interesting to know whether the effect is observable already in children younger than 3 years of age, as precursory skills of attentional control have been shown to develop already in infancy (Fiske et al., 2021; Fiske & Holmboe, 2019). Notably, however, in view of the relatively high exclusion rate in young preschool children with the current task (see Section 2.4 and Table S1), a new task would need to be developed to test younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-infancy (nine to twelve months of age) is characterized by synaptogenesis in both primary and associative cortical regions, relative maturity of pyramidal neurons, disappearance of the subplate remnant, gradual delineation of cortical areas and the beginning of myelination of the cortical pathways (Kostovic, Sedmak and Judaš, 2019). is underlies the development of cognitive functions in interaction with the social environment and the rst appearance of advanced cognitive abilities associated with the prefrontal cortex (PFC) (Diamond, 1990(Diamond, , 1991Fiske and Holmboe, 2019;Fiske et al, 2021).…”
Section: 3mentioning
confidence: 99%